2000
DOI: 10.1176/appi.ajp.157.6.975
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine, Diabetes Mellitus, Weight Gain, and Lipid Abnormalities: A Five-Year Naturalistic Study

Abstract: The results support the hypotheses that patients treated with clozapine experience significant weight gain and lipid abnormalities and appear to be at increased risk for developing diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
393
7
34

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(456 citation statements)
references
References 40 publications
22
393
7
34
Order By: Relevance
“…In keeping with this, body weight was not affected when haloperidol was administered orally to male rats for three or six weeks (Minet-Ringuet et al, 2005; Pouzet et al, 2003), and was even suppressed under the longer treatment period of 80 weeks (Yoshida et al, 1995 51(7--8): 1129--1136, 2006 adipose tissue under the influence of hormonal changes such as increased serum levels of insulin (Cusin et al, 1990), corticosterone (Guillaume-Gentil et al, 1993) and growth hormone (Ho et al, 1996) and reduced serum levels of thyroid hormones (Kyle et al, 1966), IGF-1 (Shaw et al, 2003), and testosterone (Mudali and Dobs, 2004). However, our data show that not only does chronic haloperidol administration to male rats have no effect on body weight or food intake, it also has no effect on adiposity or the serum levels of many of the hormones that modulate body composition.…”
Section: Effect Of Haloperidol or Risperidone On Body Tissue Compositionmentioning
confidence: 83%
See 1 more Smart Citation
“…In keeping with this, body weight was not affected when haloperidol was administered orally to male rats for three or six weeks (Minet-Ringuet et al, 2005; Pouzet et al, 2003), and was even suppressed under the longer treatment period of 80 weeks (Yoshida et al, 1995 51(7--8): 1129--1136, 2006 adipose tissue under the influence of hormonal changes such as increased serum levels of insulin (Cusin et al, 1990), corticosterone (Guillaume-Gentil et al, 1993) and growth hormone (Ho et al, 1996) and reduced serum levels of thyroid hormones (Kyle et al, 1966), IGF-1 (Shaw et al, 2003), and testosterone (Mudali and Dobs, 2004). However, our data show that not only does chronic haloperidol administration to male rats have no effect on body weight or food intake, it also has no effect on adiposity or the serum levels of many of the hormones that modulate body composition.…”
Section: Effect Of Haloperidol or Risperidone On Body Tissue Compositionmentioning
confidence: 83%
“…Moreover, atypical antipsychotic drugs have been increasingly used for the clinical management of other conditions such as mania, bipolar disorder, dementia, and severe anxiety (Hellewell, 2006 andNemeroff, 2005). However, one serious disadvantage of atypical antipsychotic drugs is an increased propensity of excessive weight gain and diabetes mellitus associated with their use (Conley and Kelly, 2005, Green et al, 2000and Henderson, 2001, although the degree of weight gain induced by the different atypical agents may range significantly. For example, the atypical antipsychotics clozapine and olanzapine have been reported to induce substantial weight gain of approximately 4 kg over ten weeks period while others like sertindole and risperidone had more modest effects with mean weight gain of 2.92 kg and 2.10 kg respectively after ten weeks of treatment (Allison et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that psychotropic drugs which cause weight gain, activate the TNF-α system (14) and thus the TNF-α system is an early and sensitive indicator of weight gain (15 (17). (20) (19,(23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%
“…4 In another study, patients who already had diabetes required to be switched from an oral hypoglycaemic agent to insulin or alternatively for their insulin dosage to be increased approximately two-fold. 5 Where diabetes occurs in association with these drugs, it usually presents soon after commencement of treatment -59% of cases within three months and 84% within six months -and resolves once the drug is withdrawn. 12 Where DKA has occurred, the majority of cases were within six months of commencing treatment and resolved upon withdrawal of the drug.…”
Section: The Association Between Atypical Antipsychotic Drugs and Diamentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] There have been numerous case reports in the literature of new-onset diabetes following the commencement of atypical antipsychotics, particularly clozapine and olanzapine. Many other cases have been reported through the clozapine patient monitoring service.…”
Section: The Association Between Atypical Antipsychotic Drugs and Diamentioning
confidence: 99%